The bacteria presence on utensils and worktop surfaces in food court / Nurul Shuhada Sabaruddin - Sabaruddin, Nurul Shuhada (2017)
Introduction: The contaminated utensils and worktop surfaces are known as one of the causes of food contamination. The study was conducted to identify the presence of Escherichia coli and Staphylococcus aureus on the utensils and worktop surfaces also to identify the hygiene level in the premise. Methodology: The environmental swab had been done to all samples of the utensils. Total samples are 126 samples of swab from seven utensils of the six premises. The swabs had been done three time each utensils to take the average numbers of colonies. For the hygiene level of premise, the premise inspection format form that had been accredited by Ministry of Health had been used. Result: The average numbers of Escherichia coli colonies ranged from 2.0- 269.3 (cfu/ml). However, there are two negative results that had been recorded. For the Staphylococcus aureus the average numbers of colonies are ranged from 1.0 - 186 (cfu/ml). All the result of Staphylococcus aureus showed the positive result. The hygiene level of the premise ranged from 53% to 86%. The highest level was recorded in the premise that has 86% of evaluation marks. All premise had the hygiene level above 50%. Conclusion: The presence of Escherichia coli and Staphylococcus aureus should be detected early to avoid the food borne illness from occur. The results of the average number of colonies were in the acceptable limit. For the hygiene level all the results were above the 50% and there was no premise that advises to close immediately according to the low result.